(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The provision of business capital to former terrorism convicts as a deradicalization program carried out by the Central Java Regional Police has been running but has not been in accordance with the desired expectations. This is due to the lack of supervision from members of the Police on ex-terrorism convicts (Man to Man) who received business capital, and it was even found that some ex-terrorism convicts used the money to support their group activities. The problem in this research is to understand and analyze the repositioning of the deradicalization program of former terrorism convicts in restoring the notion of nationalism and the state according to Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Eradication of Criminal Acts of Terrorism. The method in this research is descriptive analytical with a normative juridical approach. The results of this study are in the form of repositioning the deradicalization program of former terrorism convicts in restoring nationalism and state ideology according to Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Eradication of Criminal Acts of Terrorism. Terrorism is a crime related to radicalism, so deradicalization and counter-radicalism programs must go hand in hand to become an integral part of the criminal justice system and criminal law politics in efforts to combat terrorism. In order for the deradicalization program to run properly, effectively and successfully, a sustainable deradicalization strategy for the long term is needed with a comprehensive approach, both legal (law enforcement) and soft power approaches that involve several strategic aspects such as economy, religion, education and socio-culture. Of course, it is synergized with counter-radicalism programs as an effort to prevent and counter terrorism. Keywords: Deradicalization; Radicalism; Terrorism